Development Plan of Unmanned System and Development Status of UUV Technology in Foreign Countries - Jin-Yun Wang; Wei Ke (Universitas Muhammadiyah Yogyakarta, 2022)
The future battlefield will be unmanned combat as the leading role, and the unmanned underwater vehicle (UUV) will play an important role in the future underwater battlefield. In order to maintain its maritime strategic advantages, the U. S. military has formulated a long-term development plan for the unmanned aerial vehicle (UAS) in recent years. The technology of unmanned underwater vehicles (UUV), which is characterized by strong endurance, high mobility, and high covert attack, has become the future development trend. In addition, Russia, with its strong industrial foundation and technical strength, has introduced its latest development status. At last, the latest research results of the new concept of surface/underwater cross-medium submarine were introduced. The results show that the new intelligent cross-medium submarine will become the mainstream of future development. The research provides a reference for the development of unmanned equipment in China.